Inkjet printed hydrophobic microfluidic channelling on porous substrates - Nguyen, Duy Linh; Lyashenko, Alexandra; Ucuncu, Meliksah; Schmitt-Lewen, Martin; Weber, Alexander; Henn, Andreas; Loeprich, Simon; Doersam, Edgar (Journal of Print and Media Technology Research, 2023)
Since some years, several research institutes, institutions and companies are working on the realization of electronic components by innovative methods, which can lead to cost-effective, simplified and flexible production of such products. Among other low-cost technologies such as coating and vapor deposition, printing as an additive structuring process is one focus of research. Another interesting additive printing-related method is cold foil transfer technology or also so-called cold foil stamping. The cold foil transfer technology is conventionally used in the finishing step for various, mostly decorative, printing products. For a real metal effect to be obtained in graphic arts printing so-called cold foils are used, which in most cases have an aluminium layer. The metal is applied by vapor deposition with high demands on the polyester foil properties, so that the metal particles are close together and thus set up a thin homogeneous conductive aluminium layer in the nanometer range. The fact that the cold foils have a metal layer has led to the idea of using this printing method for electronic applications using its conductivity. The following criteria are important for using cold foil transfer processes for printed electronics: electrical conductivity, reproducibility and reliability of such metal layers, especially depending on different printing process settings. In this research, the cold foil is transferred to a substrate in a sheet-fed offset printing press. The samples are measured by using a contactless measurement method. The experiments show a medium to low sheet resistances of the transferred aluminium layer. Furthermore, the conductivity of the aluminium areas on the substrate depend on their location on the much larger substrate sheet. The objective of this research – application of the cold foil transfer technology and determination of its process boundaries for the use in the electronics field – could be confirmed.